A Comprehensive Review on the Intersection of Artificial Intelligence and Organizational Agility - Thiyagarajan, Geetha Priya; Kumar, P. Praveen; Monica, Benita S (Journal of Neonatal Surgery, 2025)
In the fast-changing technology environment, the most critical question that faces any organization is not "whether" to go for corporate agility but to "what degree" and "how best" to develop that flexibility. In addition, the organizational agility concepts become significant from the time of COVID-19 since new ways are required by organizations for the improving employee engagement, building organizational performance and capabilities for assisting their competitiveness and delivering on their business strategy. Economic, legislative, and political pressures and market competition served a pivotal role in the need for the increased strategic and organizational agility. Artificial Intelligence (AI) enhances organizational agility through digital capabilities in this study. As organizations integrate AI tools, they can enhance internal processes, simplify operations, facilitate efficient decision-making, as well as be more responsive to market dynamics and customer needs externally. The organization’s transformation is determined by AI tools to leverage the firm’s digital capabilities, thereby the firm could become more agile in terms of internal processes and the external environment challenges. An exploration of how Artificial Intelligence (AI) technologies are transforming businesses to succeed in rapidly changing environments is presented in this paper. In this study, we highlight the enabling role of AI in fostering operational, strategic, and portfolio agility in conjunction with critical agility frameworks, which includes the machine learning, Internet of Things (IoT) and neural networks. Furthermore, the paper demonstrates AI's transformative potential in organizations by discussing its impact on decision-making, innovation, and resource allocation. In order to build resilient, competitive, and adaptive enterprises, artificial intelligence-driven solutions must be incorporated.